Workplace Health and Wellbeing during and beyond COVID-19 - Blake, Holly (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this reprint, we focus on health and wellbeing in the workforce within the context of the global COVID-19 pandemic, and the post-pandemic era. We begin by exploring the impacts of the pandemic on diverse occupational groups, considering the broader mental health impacts of the pandemic, reactions to national lockdowns and behavioural strategies to control the spread of the virus, such as social distancing and self-isolation, attitudes towards infection control and work presenteeism. Next, we explore the relationship between job factors, working conditions and psychological wellbeing of employees. The papers that follow examine changes in work patterns and locations, such as remote, hybrid, and on-site working, the impact of organizational climate on mental wellbeing, and organizational approaches to return-to-work after lockdown. Finally, we present innovative organizational- and individual-level pandemic mitigation interventions, including SARS-CoV-2 testing services and infection control approaches, digital mental health support, and COVID-19 Vaccine Education. This collection demonstrates the breadth of research on work, health and wellbeing, during and beyond the COVID-19 pandemic, covering workforce impacts and workforce interventions in various countries and settings. Learning from this research will help to build global preparedness for future pandemics and foster resilience for responding in times of crisis and uncertainty.